Peminjaman Inkubator Gratis Bagi Bayi Prematur - Pipin Sumantrie; Martalina Limbong (Jurnal Surya Masyarakat, 2020)
The United Nations (UN) in 2010 report entitled “Born Too Soon, The Global Action Report on Preterm Birth” placed Indonesia in fifth place as the country with the highest number of premature babies in the world. This was supported by data from the Central Bureau of Statistics in 2016, saying the infant mortality rate (IMR) reached 25 deaths per 1,000 babies born. The implementation of the community service (PKM) is through a strategic approach to the community in the form of promoting free incubator lending to families with premature babies. The approach is carried out directly (direct approach) by using effective communication to health workers, as well as to urban villages around the work area. With the free incubator, many parents who have LBW babies feel helped and are very grateful, the incubator lending process that has been loaned to parents ranges from 1 to 2 months, but there are also families who borrow more than 3 months. This is because the baby's condition is difficult to develop. With the availability of free portable incubator loans carried out by the Surya Nusantara Nursing Academy Free Incubator Volunteers, in collaboration with the Indonesian Premature Baby Foundation, the people of Pematansgiantar and its surroundings feel helped, and are very grateful, not only that the babies who feel comfortable being in the incubator but also the parents also who feel happy, and they do not worry about the development of their baby. They also do not need to experience stress in connection with funding for the care of premature babies, because the incubator and blue light phototherapy equipment is lent out for free without being charged a penny.